2020
DOI: 10.7759/cureus.6747
|View full text |Cite
|
Sign up to set email alerts
|

Success of Coronal Pulpotomy in Permanent Teeth with Irreversible Pulpitis: An Evidence-based Review

Abstract: Vital pulp therapies have been used in primary teeth and immature permanent teeth. However, with the advent of new bioactive material, the paradigm is shifting toward permanent teeth with mature apices of roots. There are many prospective and retrospective studies, randomized controlled trials, and systematic reviews that report coronal pulpotomy with bioactive material in permanent teeth with pulpal pathosis proved to be as successful as root canal therapy (RCT). Coronal pulpotomy is cost-effective, not very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 36 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…Comprehensive systematic review by Alqaderi et al evaluated the success rate of cervical pulpotomy in mature permanent teeth with irreversible pulpitis. Overall success rate at one year was 94% and 92% at two years 12 .…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Comprehensive systematic review by Alqaderi et al evaluated the success rate of cervical pulpotomy in mature permanent teeth with irreversible pulpitis. Overall success rate at one year was 94% and 92% at two years 12 .…”
Section: Discussionmentioning
confidence: 86%
“…20 Similarly Simon et al, performed pulpotomy on permanent molar teeth using MTA and showed 82% success at the end of 24 months 19 . A systematic review by Li et al reported clinical success rate of 95% with MTA pulpotomy in a study evaluating the comparison between MTA vs CaOH at 12 months 12 . Aguilar and Linsuwanont compared different types of vital pulp therapies in a systematic review and found MTA pulpotomy with the highest success rate of 96.6% at three years of follow-up 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some pulp-capping materials have been reported to have inflammation-modulating effects (Giraud et al, 2019), their functionalisation with modulating molecules could boost their regenerative properties in terms of macrophage polarisation and complement system activation. Arguably, adding inflammation-modulating molecules to the capping materials could even open new horizons for mature teeth pulpotomy, currently approached as a provisional rather than a full alternative for RCT (Li et al, 2019;Sadaf, 2020).…”
Section: Potential Clinical Applicationmentioning
confidence: 99%